AN ANALYSIS ON CSR REPORTING PRACTICES OF PLN (PERUSAHAAN LISTRIK NEGARA) - Anas Febrian; Tri Siwi Agustina (UPT Publikasi Ilmiah UNISBA, 2024)
This article examines the Corporate Social Responsibility (CSR) reporting practices of PLN (Perusahaan Listrik Negara). The objective of this study is to analyze the allocation of CSR funds and the amount spent on various CSR activities by PLN. Using a descriptive research design and content analysis method, this research reveals insights into PLN's CSR initiatives. The results indicate that in the observed financial years of 2021 and 2022, PLN showed variations in the allocation and utilization of CSR funds. The results indicate that in the observed financial years of 2021 and 2022. Moreover, the analysis highlights the concentration of CSR spending in areas such as PLN Edu library, informal schools, and the PLN Cares for Education program.